Osteosarcoma of mandible: Detailed radiographic assessment of a case - Piyush Arora; Farzan Rehman; K L Girish; Manpreet Kalra (Wolters Kluwer Medknow Publications, 2013)
Osteosarcoma (OS) is a malignant connective tissue tumor originating from bone and is the most common primary bone malignancy of long bones but seldom arises in jaw bones. Osteosarcoma of jaws is frequently seen arising in the second and third decade as compared to earlier occurrences in other bones and show a slight predilection for body of mandible. It is a highly malignant tumor with varied radiographic features. We present a case with detailed radiographic assessment using intraoral radiograph, computed tomography (CT), 3-D CT, CT angiography techniques and histological evaluation.